PENGARUH PENAMBAHAN BAHAN PLASTIK MIKA SEBAGAI FILLER PADA CAMPURAN (AC-WC) DENGAN PENGUJIAN MARSHALL - Misbah, Misbah; Wahyuni, Serli (Jurnal Teknologi dan Vokasi, 2024)
In terms of improving road pavement, there are several things that must be paid attention to, namely the quality of the aggregate used, the method of implementation, and the quality of the asphalt. The method that is often used to improve the quality of asphalt is by adding additives. These include charcoal, plastic, and others. Plastic has many benefits but also has negative sides, especially plastic waste. However, plastic waste opens up opportunities to be used in the field of road construction. In research, mica plastic can be used because it has characteristics that are stronger than other types of plastic and more elastic when heated. Mica plastic is thermoplastic, not reactive at room temperature, except for certain types of solvents which can cause damage. In this research the author tries to determine the effect of adding mica plastic and determine the aggregate gradation characteristics of the Asphalt Concrete Wearing Course (AC-WC) mixture based on the Marshall test. The results of this test show that all experiments with the addition of mixing carried out for the addition of 0% mica plastic obtained an optimum asphalt content of 5.50%, with an addition of 2% the optimum asphalt content was 5.50%, with the addition of mica plastic as much as 5.50%. 4% cannot be used because the test results do not meet specifications, whereas with the addition of 6% mica plastic, the optimum asphalt content value is 6.25%. So, the best effect of adding mica plastic to hot asphalt (AC-WC) is mixing plastic levels of 0% and 2% with the optimum asphalt content obtained at 5.50%. For the Stability, Flow, VMA, and VFB values, the average results meet the specified specifications, while for the MQ and VIM values, the values ​​increase and decrease at each specified percent, thus affecting the results and performance of the asphalt used. So, it can be concluded that adding mica plastic to the asphalt mixture cannot be used, further research is needed to get more accurate results.